Consumer Preference on the Use of Eco-Friendly Bag: a Green Marketing: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The study aimed to determine the preference of the consumers using an eco-friendly bag, andwith the help of the level of awareness of consumers in green marketing, purposive samplingwas employed in General Luis Novaliches Quezon City. The quantitative research designthrough questionnaires figured out that there is a high level of awareness among consumersusing an eco-friendly bag. With a high level of awareness of the environmental problems of theworld, waste, and pollution management, the consumer supports the advocacy of greenmarketing, the advocacy of using eco-friendly bags rather than conventional bags that causeenvironmental problems. Furthermore, results showed that consumers preferred the price,durability, and appearance of eco-friendly bags. The level of awareness is the main reason forconsumers to use eco-friendly bags brought on by environmental problems and pollution.The suggested level of green marketing awareness of consumers utilizing eco-friendly bags isaddressed in light of the study's findings. Consumers who use eco-friendly bags demonstratehigh levels of environmental awareness in three ways: (1) environmental benefits (eco-friendlybags can be reused and are stronger and more durable than conventional plastic bags,eliminating the need for single-use plastic bags that have been shown to harm theenvironment); (2) public acceptance (the majority of people who use eco-friendly bagsunquestionably accept the use of eco-friendly bags);The researcher advises consumers to support green marketing advocacy and use eco-friendly bags when shopping for necessities in order to persuade other customers to do thesame. Using eco-friendly bags will help to reduce global environmental problems such assewerage pollution because typical plastic bags take a long time to break down, which resultsin pollution. Eco-friendly bags have a high level of consumer acceptance for their appearance.Because using eco-friendly bags reduces the cost of the bags they use when shopping andpurchasing items, consumers are more likely to do so.
Keywords: Marketing